Corporate Entrepreneurship And Employees' Work Performance: The Impact Of Individual And Organisational Factors - Ewe Keat, Kong (2012)

(untitled)
With increasing globalization and fast pace of technology advance in recent decades, there is a need to ingrain corporate entrepreneurial spirit amongst Malaysian workforce as Malaysia is striving to become an innovation led economy.